Analysis of the potential and limitations of microwave radiometry for the retrieval of sea surface temperature: Definition of MICROWAT, a new mission concept. Issue 6 (19th June 2013) - Prigent, C.; Aires, F.; Bernardo, F.; Orlhac, J.‐C.; Goutoule, J.‐M.; Roquet, H.; Donlon, C.
Abstract : [1] The sensitivity of passive microwave observations to the sea surface temperature (SST) is carefully analyzed, with the objective of designing an optimized satellite instrument, MICROwave Wind And Temperature (MICROWAT), dedicated to an "all‐weather" estimation of the SST at high spatial resolution (15 km). Our study stresses the importance of low‐frequency observations around 6 GHz for accurate SST retrieval. Compared to the 11 GHz channel, the 6 GHz channel provides more sensitivity to the low SSTs and offers lower instrument noise, thanks to possibly broader channel bandwidths. However, it requires much larger antenna size for a given spatial resolution. Two instrument concepts have been suggested, one using a classic real aperture antenna and the other using synthetic interferometric antennas. This first analysis shows that 2‐D interferometric systems would be very complex and would not satisfy the user requirements in terms of SST accuracy. A 1‐D interferometric system could be proposed, but its development requires additional investigation. A dedicated conical scanner onboard a microsatellite with a 6 m antenna and channels at 6.9 and 18.7 GHz (both with V and H polarizations) can provide an SST accuracy of 0.3 K with a 15 km spatial resolution, with today's technology. Key Points: Low microwave frequencies are required for sea temperature estimate Good spatial resolution requires large classical antennas or interferometers SST can be obtained with 0.3K accuracy even under cloudy conditions